Genome sequences of novel members of previously described DNA and RNA virus families, isolated from feces of a drill monkey in Nigeria (2020)
The genomes of seven novel members of previously described DNA and RNA virus families are described here. These viruses were recovered using a viral metagenomic approach from the stool of a drill monkey (Mandrillus leucophaeus) housed in a sanctuary in Cross River State, Nigeria.